REALISM AND NATURALISM IN AMERICAN LITERATURE - Ergashaliyeva Madina Abduqahhor qizi,; Khamitov Eldorbek Erkin o'g'li, (Лучшие интеллектуальные исследования, 2024)
This article overview of the concepts of realism and naturalism in American literature and explores their significance and impact on the literary landscape. Realism and naturalism emerged as prominent literary movements in the late 19th and early 20th centuries, reflecting the societal changes and intellectual currents of the time. This study aims to examine the key characteristics, similarities, and differences between realism and naturalism, and to analyze their representation in American literary works.